The Implementation of Cooperative Learning Through Teams Games Tournament (TGT) Model to Improve Students’ Speaking Ability - Moh. Mahmud; Ahmad Faruk (IAI Darussalam, 2021)
The objective of this research is to know the implementation of cooperative learning through (TGT) model in teaching English to improve students’ speaking ability. This was classroom action research (CAR) it was objectives to repair teaching-learning. The methods of collecting primary data are observation and test. The methods of supporting data were obtained from interviews and documentation. Based on the result and data analysis it can be concluded that the teacher already applied the team's games tournament (TGT) and good enough preparation. The students get significant scores. It can be seen that before using teams games tournament students’ mean score was 59.8, in Cycle 1 students’ mean score was 72 and students’ mean score in Cycle 2 was 79. Finally, it is a great number that the implementation of cooperative learning through teams games tournament (TGT) in teaching speaking is success categories and the teacher should give more exercise in English to the students to develop their skill in teaching speaking, give motivation student’s continually, the teacher should make a good relationship with students to get result of speaking material maximally.